1997
DOI: 10.1177/009164719702500207
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Treatment on God Image and Personal Adjustment, and Correlations of God Image to Personal Adjustment and Object Relations Development

Abstract: This study examined the effectiveness of a religiously-based, object relations oriented psychotherapy treatment program. Effectiveness was measured by changes in personal adjustment and God image for a group of religious patients. An inpatient sample (N = 99), with the predominant diagnosis of major depression, was followed over the course of inpatient treatment and a year of outpatient treatment following hospitalization. Measures were administered at admission and discharge (N = 99), six months after dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
2
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 26 publications
2
49
2
5
Order By: Relevance
“…The items were rated on a 7-point Likerttype scale with the response options (1) never, (2) almost never, (3) rarely, (4) sometimes, (5) often, (6) almost all the time, and (7) always. Although a one-factor structure of the REQ has previously been used by other researchers (Brokaw & Edwards, 1994;Tisdale et al, 1997), an examination of the factor structure for the present study's Norwegian sample found better support for a two-factor structure (see appendix). Consequently, a two-factor structure with positive and negative REQ was used in this study, and Cronbach's alpha for Positive REQ was .96 and for negative REQ .61.…”
Section: Methodscontrasting
confidence: 50%
“…The items were rated on a 7-point Likerttype scale with the response options (1) never, (2) almost never, (3) rarely, (4) sometimes, (5) often, (6) almost all the time, and (7) always. Although a one-factor structure of the REQ has previously been used by other researchers (Brokaw & Edwards, 1994;Tisdale et al, 1997), an examination of the factor structure for the present study's Norwegian sample found better support for a two-factor structure (see appendix). Consequently, a two-factor structure with positive and negative REQ was used in this study, and Cronbach's alpha for Positive REQ was .96 and for negative REQ .61.…”
Section: Methodscontrasting
confidence: 50%
“…In this same regard, the defense mechanism of suppression is more commonly observed in the collectivist cultures in order to maintain harmony, whereas repression may be more commonly observed in the individualist cultures (Hsu, 1949;Nagai, 2007). Along the same line of thinking comes the Eastern concept of self that is viewed as a constellation of internal representations of relationships with others, thus leading to multiple self and object representations experienced as the extensions of families and communities (Tisdale, Key, & Edwards, 1997). The concept of self in the individualist Western cultures is constrained by selfawareness, self-control and self-esteem, so much so that the Dalai Lama, who is said to embody the Asian culture and Eastern religion and spirituality, could not grasp the meaning of self-esteem (see Epstein, 1995: p. 177).…”
Section: Religion: a Subset Of Culturementioning
confidence: 99%
“…Support is also offered for researchers' findings that psychotherapeutic change affects and is affected by spiritual concerns (I3enson & Spilka, 1973;Spilka, 1964;Tisdale et al, 1997). When an individual makes a decision to enter into the therapeutic process, he or she brings the whole person into the therapeutic relationship, including religious faith and/or personal spirituality.…”
Section: Implications For Counselingmentioning
confidence: 99%
“…Tisdale et al (1997) explored the impact of inpatient treatment on the God image and personal adjustment of 99 evangelical Christians whose predominant diagnosis was major depression. The study continued to follow the patients in outpatient treatment.…”
mentioning
confidence: 99%